2014
DOI: 10.1371/journal.pone.0085584
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Stem Cell-Associated Intermediate Filament Nestin in Malignant Proliferation of Non-Small Cell Lung Cancer

Abstract: BackgroundNestin is associated with neoplastic transformation, but the mechanisms by which nestin contributes to invasion and malignancy of lung cancer remain unknown. Considering that proliferation is necessary for malignant behavior, we investigated the mechanism of nestin action in association with the proliferative properties of non-small cell lung cancer (NSCLC).MethodsNestin expression was examined in NSCLC specimens and cell lines. Associations with clinicopathological features, including prognosis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 39 publications
2
28
0
Order By: Relevance
“…Here, we first established that nestin is expressed in 34.4% of ESCC samples in Chinese population, a result similar to that reported for lung squamous cell carcinoma (35.5%) and our previous findings in NSCLC [19,29]. Consistent with these findings, we also detected nestin mRNA and protein in the ESCC cell lines, Eca-109 and TE-1.…”
Section: Discussionsupporting
confidence: 91%
“…Here, we first established that nestin is expressed in 34.4% of ESCC samples in Chinese population, a result similar to that reported for lung squamous cell carcinoma (35.5%) and our previous findings in NSCLC [19,29]. Consistent with these findings, we also detected nestin mRNA and protein in the ESCC cell lines, Eca-109 and TE-1.…”
Section: Discussionsupporting
confidence: 91%
“…In tumorigenic and neural progenitor/stem cells as well as the embryonic mouse heart, cell cycle re‐entry facilitated by the intermediate filament protein nestin was associated with the recruitment of the signalling axis PI3K/PDK/AKT (Liu et al, ; Chen et al, ; Xue & Yuan, ). Moreover, PI3K/PDK/AKT signalling was reported to promote the cell cycle re‐entry of embryonic and adult cardiomyocytes (Beigi et al, ; Evans‐Anderson, Alfieri, & Yutzey, ; Lin et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Nestin is a member of the class VI family of intermediate filament proteins originally identified in neural progenitor/stem cells of the developing central nervous system (Dahlstrand, Zimmerman, McKay, & Lendahl, ; Lendahl, Zimmerman, & McKay, ). However, additional studies revealed that nestin was not a unique marker of neural progenitor/stem cells as the intermediate filament protein was detected in fibroblasts (e.g., heart, kidney), vascular smooth muscle and endothelial cells, pre‐existing cardiomyocytes bordering the peri‐infarct region of the ischemically damaged human/rodent heart, skeletal muscle, and tumorigenic cells (Béguin, Gosselin, Mamarbachi, & Calderone, ; Carlsson, Li, Paulin, & Thornell, ; Chen et al, ; El‐Helou et al, ; Hertig et al, ; Ishiwata et al, ; Meus, Hertig, Villeneuve, Jasmin, & Calderone, Mokry et al, ; Oikawa, Hayashi, Maesawa, Masuda, & Sobue, ; Sejersen & Lendahl, ; Tardif et al, ; Tomioka et al, ; Vaittinen et al, ). Biologically, nestin plays a direct role in the proliferation and migration of normal and tumorigenic cells (Béguin et al, ; Chen et al, ; Liang et al, ; Ishiwata, Matsuda, & Naito, ; Matsuda et al, ; Meus et al, ; Tardif et al, ; Xue & Yuan, ).…”
Section: Introductionmentioning
confidence: 99%
“…NESTIN is considered to be a biomarker to identify CSCs in mesenchymal and epithelial neoplasms and has key roles in differentiation, proliferation, migration, invasion, metastasis, and survival of malignant neoplastic cells, through regulation of cytoskeleton and progenitor cells (Matsuda et al., ; Neradil & Veselska, ; Sahlgren et al., ). Its expression can be associated with increased risk of high malignancy and poor prognosis in many types of cancer, including non‐small‐cell lung cancer, gastric cancer, and esophageal squamous cell carcinoma (Chen et al., ; Dhingra et al., ; Li, Lai, Fan, Shen, & Che, ; Zhong et al., ).…”
Section: Discussionmentioning
confidence: 99%